Value chain and nutmeg farmers’ welfare in Morella, Central Maluku, Indonesia - VILIA GLAUDYA PAAYS; MUSRAN MUNIZU; ARIADY ARSAL (Smujo International, 2026)
Abstract. Paays VG, Munizu M, Arsal A. 2026. Value chain and nutmeg farmers’ welfare in Morella, Central Maluku, Indonesia. Asian J Agric 10 (1): g100121. https://doi.org/10.13057/asianjagric/g100121. Nutmeg is one of Indonesia’s high-value plantation commodities and plays an important role in supporting rural livelihoods. However, despite its economic potential, many smallholder nutmeg farmers still experience limited welfare improvements due to weak integration within traditional value chain systems. In many producing areas, farmers face constraints such as limited market access, price uncertainty, low bargaining power, and weak institutional support. These conditions reduce farmers’ ability to capture the value created along the nutmeg value chain and ultimately limit improvements in income and welfare. Therefore, understanding how value chain performance influences farmer income and welfare is essential for developing effective strategies to improve smallholder livelihoods. This study aims to analyze the direct and indirect relationships between the nutmeg value chain, farmer income, and farmer welfare in Morella Village, Central Maluku District, Indonesia, with income functioning as a mediating variable. The research employed a quantitative explanatory design using survey data collected from 84 nutmeg farmers. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to examine the relationships among the variables and test the mediating role of income. The results show that value chain performance has a positive and significant effect on both farmer income and farmer welfare. Improvements in value chain activities such as production management, logistics, marketing, and institutional support contribute to increased farmer income and improved welfare conditions. In addition, income significantly influences farmer welfare and partially mediates the relationship between value chain performance and welfare outcomes. However, the direct effect of the value chain on welfare is stronger than the indirect effect through income, indicating that structural improvements in the value chain contribute to welfare beyond income increases alone. These findings highlight the importance of strengthening the nutmeg value chain to enhance smallholder welfare. Policies that improve market access, develop post-harvest processing, strengthen farmer institutions, and promote technological adoption are essential to ensure that value creation within the nutmeg value chain translates into sustainable income growth and improved welfare for smallholder farmers.